2015
DOI: 10.3934/publichealth.2015.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Resourcefulness, Desperation, Shame, Gratitude and Powerlessness: Common Themes Emerging from A Study of Food Bank Use in Northeast Scotland

Abstract: There is growing policy maker and public concern about current trends in food bank use in Scotland. Yet little is known about the experiences of those seeking help from food banks in this country. This research aimed to address this issue by studying the use and operation of a food bank situated in a rich northeast city during January and June 2014. The study aimed to establish who was seeking help from the food bank, their reasons for doing so, and what those who did thought of, and dealt with the food they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 33 publications
(59 reference statements)
6
92
0
Order By: Relevance
“…Ethan's account highlights the dread associated with realising there is a need to visit a foodbank, reflecting existing literature (Douglas et al, 2015;Garthwaite, 2016a). He explains how this stopped him coming in the past (even during a 'really, really bad week') and acknowledges the role of the media in reinforcing the image of clients taking advantage of foodbanks (in line with Wells and Caraher's (2014) review of UK media's foodbank reporting).…”
Section: Resultsmentioning
confidence: 85%
“…Ethan's account highlights the dread associated with realising there is a need to visit a foodbank, reflecting existing literature (Douglas et al, 2015;Garthwaite, 2016a). He explains how this stopped him coming in the past (even during a 'really, really bad week') and acknowledges the role of the media in reinforcing the image of clients taking advantage of foodbanks (in line with Wells and Caraher's (2014) review of UK media's foodbank reporting).…”
Section: Resultsmentioning
confidence: 85%
“…The 20 papers included in this review are all empirical studies that collected some form of 110 qualitative data from individuals who had received food assistance from food banks. Seven studies 111 used one qualitative method 4,10,20,24,27,35,36 , six studies used more than one qualitative method 21, 23, 112 26,30,31,33 , five used a mix of qualitative and quantitative methods 25,28,29,32,37 , and two studies used 113 multiple qualitative methods along with quantitative methods 22,34 . The range of qualitative methods 114 used can be seen below in Table 2.…”
Section: Summary Of Studies 109mentioning
confidence: 99%
“…The studies included ranged from published 126 literature 4, 10, 21, 27, 29-31, 33, 34, 36, 37 , to theses 20,[22][23][24][25][26]28 and organisation reports 32,35 and were published 127 between 1999 and 2015. Most were conducted in Canada 10,[20][21][22][23][24]29 , followed by the United 128 Kingdom (UK) 4,[32][33][34][35] , the United States of America (USA) 27,30,36,37 , New Zealand 25, 28 and the 129 Netherlands 26,31 . There were no Australian studies found that met the criteria for this review.…”
Section: Summary Of Studies 109mentioning
confidence: 99%
See 2 more Smart Citations